Effects of Grain Morphology on Nonlinear Conversion Efficiency of Random Quasi-Phase Matching in Polycrystalline Materials - Kefei Liu; Kai Zhong; Zhantao Lu; Degang Xu; Jianquan Yao (IEEE Photonics Journal, 2020)
Monte-Carlo simulations were performed on the efficiency of random quasi-phase matching (RQPM) nonlinear optical frequency conversion in polycrystalline materials to study the detailed effects of the statistical grain morphology. The second harmonic generation (SHG) process was taken for example based on random structures generated by a realistic grain growth model, and the effective nonlinear coefficient was rigorously derived by tensor transformation in randomly rotated coordinates. The effects of average grain size, standard deviation, and sphericity on SHG efficiency were figured out to conclude that the grain-size deviation plays the most important role in RQPM efficiency and the optimal grain size is smaller than the coherence length. The impacts of fundamental wavelength variation were also investigated. These results reveal how the RQPM process is affected by statistical and nonlinear optical laws, which enrich the RQPM theory and provide criteria for polycrystalline material processing in specific nonlinear applications.